Spain´s Role in the European Common Foreign Policy: The last Decade (2001-2011) - Guinea, Mercedes (UNISCI Discussion Papers, 2011)
Spain has undergone profound transformations as result of its accession to the European Union in 1986, on a steady process of europeanization. This article examines the bidirectional influence between Spanish foreign policy and European Common Foreign and Security Policy between 2001 and 2011 as an example of europeanization. During this period the Spanish Government was led by two political parties, the Conservative Party (PP) and the Socialists (PSOE), which had different visions about Spanish role in Europe and Spanish foreign policy. We will analyze these two distinct phases from different points of view: international and European contexts, both Governments visions and perceptions of European political project, their international and European alliances, paths of Europeanization (top-down y bottom-up), and Spanish participation in European Security and Defence Policy. We will pay special attention to the periods when Spain was at the helm of the European Union, in 2002 and 2010.
Keywords: Spain; European Union; Spanish foreign policy; CFSP; Europeanization.